2009
DOI: 10.1017/s1481803500011234
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre evaluation of an emergency department asthma care pathway for adults

Abstract: Objective: We sought to determine whether a standardized emergency department (ED) asthma care pathway (ACP) for adults would be accepted by ED staff, improve adherence to Canadian ED asthma management guidelines and improve patient outcomes. Methods: Ten Ontario hospital EDs (5 intervention, 5 control) participated in a 5-month pre-post intervention study. Emergency department management, admissions, repeat ED visits and ED length of stay were compared between sites and by ACP use versus nonuse at interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…During the 5-month study period, the ACP was used in 101 visits (26%) and ranged from 6% in one of the largest sites to 60% in one of the smallest sites. Key findings of the study are outlined in Table 2 [37 ]. There were greater improvements in intervention than control sites in adherence to several components of asthma management guidelines [such as arterial blood gas measurement, use of bronchodilators by metered dose inhaler (MDI), inhaled steroids and oxygen], delivery and documentation of asthma education in the ED and referrals to specialized asthma services on discharge.…”
Section: The Emergency Department Asthma Care Pilot Projectmentioning
confidence: 98%
See 2 more Smart Citations
“…During the 5-month study period, the ACP was used in 101 visits (26%) and ranged from 6% in one of the largest sites to 60% in one of the smallest sites. Key findings of the study are outlined in Table 2 [37 ]. There were greater improvements in intervention than control sites in adherence to several components of asthma management guidelines [such as arterial blood gas measurement, use of bronchodilators by metered dose inhaler (MDI), inhaled steroids and oxygen], delivery and documentation of asthma education in the ED and referrals to specialized asthma services on discharge.…”
Section: The Emergency Department Asthma Care Pilot Projectmentioning
confidence: 98%
“…An interdisciplinary Steering Committee and Expert Content Working Group focused their efforts initially on a pathway for adults; a pediatric pathway is currently in development. The care pathway and tools were designed to support best practice and address six key objectives of asthma management outlined in Table 1 [37 ].…”
Section: The Emergency Department Asthma Care Pilot Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies reported substantial improvement in quality both in inpatient [1,11,14,18,21,32,50,53,57,60,62,68,78] and outpatient settings [13,29,37,40,42,46]. Numerous studies, including six RCTs [4,7,38,51,63,71], failed to show any positive effects on quality associated with practice guidelines [5,10,20,25,26,36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%
“…Studies found greater effect with explicit guidelines [6,13,21,23,50,55], defined as ''systematically developed statements to assist practitioner decisions about appropriate health care for specific clinical circumstances'' [27], although practice guidelines improved both processes and outcomes of care, including cost [14,29,53,62], and the results were greater for performance compared with patient outcomes. Clinician involvement in all aspects of guideline development was vital [5,46,53,73]. However, benefits of comprehensive dissemination and implementation need to be further clarified [36].…”
Section: Do Practice Guidelines Improve Quality Of Care?mentioning
confidence: 99%